2003
DOI: 10.1097/01.ta.0000053197.40145.62
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain Management of Patients with Multiple Fractured Ribs

Abstract: Based on current evidence it is difficult to recommend a single method that can be safely and effectively used for analgesia in all circumstances in patients with multiple fractured ribs. By understanding the strengths and weaknesses of each analgesic technique, the clinician can weigh the risks and benefits and individualize pain management based on the clinical setting and the extent of trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
161
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(168 citation statements)
references
References 72 publications
2
161
1
4
Order By: Relevance
“…4,6,10,15,16 The conclusion of a recent narrative review on pain management in this population stated that, based on available data, no single analgesic modality could be recommended. 11 However, recent published guidelines state that epidural analgesia is the preferred analgesic modality in patients with multiple rib fractures. 25 No meta-analysis on this topic has yet been completed.…”
Section: Résumémentioning
confidence: 99%
See 2 more Smart Citations
“…4,6,10,15,16 The conclusion of a recent narrative review on pain management in this population stated that, based on available data, no single analgesic modality could be recommended. 11 However, recent published guidelines state that epidural analgesia is the preferred analgesic modality in patients with multiple rib fractures. 25 No meta-analysis on this topic has yet been completed.…”
Section: Résumémentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Pain is recognized as a contributing factor for most of this associated morbidity, [6][7][8][9] and analgesia is a core intervention in managing these patients. 5,7 Multiple analgesic modalities have been used in patients with rib fractures, 4 such as oral analgesics, 10 intravenous opioids, 7,11 patient-controlled opioid analgesia, 12 interpleural blocks, 11 intercostal blocks, 11,13 paravertebral blocks, 11,14 and epidural analgesia. 6,7,10,11,15,16 Recent studies and metaanalyses have suggested that epidural analgesia reduces morbidity after major abdominal, [17][18][19][20] vascular, 18,20,21 and thoracic surgeries, 17,18,20 overcoming the potential risk of complications associated with this technique.…”
Section: Résumémentioning
confidence: 99%
See 1 more Smart Citation
“…But the reality that our study is not designed in randomized controlled research in order to get clearer outcomes. According to previous studies, TPVB was used successfully as a single technique for pain management in MFR patients [3,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Adequately pain relief now is considered as a cornerstone of managing MRF in blunt chest trauma patients which can help the patient breathe deeply, cough effectively as well as comply with chest physiotherapy [1,2]. Multiple analgesic modalities have been used in patients with ribs fracture such as oral analgesic agents, intravenous opioids, patientcontrolled analgesia, inter-pleural block, intercostal block, epidural block, paravertebral block [3,4]. Thoracic epidural block seemed the best analgesia for a severe chest wall injury because it provides complete analgesia allowing inspiration and coughing effectively [5].…”
Section: Introductionmentioning
confidence: 99%